2003
DOI: 10.1021/cm0340476
|View full text |Cite
|
Sign up to set email alerts
|

Control of Molecular Aggregations by Doping in Mesophases:  Transformation of Smectic C Phases to Smectic CA Phases by Addition of Long Bent-Core Molecules Possessing a Central Strong Dipole

Abstract: Compounds 1 − 3, each possessing a long bent-rod shape and a central large dipole, were designed and synthesized as dopants which transform liquid-crystal smectic C phases to smectic CA phases. The properties and the layer structures of the dopant molecules in the mesophases were investigated by polarized light microscopy, differential scanning calorimetry (DSC), and X-ray diffraction (XRD). Induction of smectic CA phases from the smectic C phases of compounds 4 − 7 was performed by doping with a small amount … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…The latter have lately attracted considerable interest due to their polar properties arising from achiral molecules [22], but only few reports towards their use as dopant molecules have been published to date. These have shown induced antiferroelectric phases in ferroelectric hosts [23,24] and enhanced chirality by addition of achiral bent-core molecules to chiral hosts [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…The latter have lately attracted considerable interest due to their polar properties arising from achiral molecules [22], but only few reports towards their use as dopant molecules have been published to date. These have shown induced antiferroelectric phases in ferroelectric hosts [23,24] and enhanced chirality by addition of achiral bent-core molecules to chiral hosts [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…According to the previous works, bent‐core H‐bonded small molecules could yield lower mesophasic transition temperatures, enthalpies, and threshold voltages than those of fully covalent‐bonded five‐ring banana‐shaped molecular analogues and H‐bonded side‐chain polymeric derivatives, which suggested that softer bent‐core intermolecular arrangements were present in both H‐bonded and small molecular designs 22–24. Regarding the small molecular systems containing two different fully covalent‐bonded components, unusual molecular arrangements and mesomorphic behaviors were developed by blending rod‐like liquid crystals with bent‐core LC dopants 25, 26. Meanwhile, the blended polymeric systems (mainly side‐chain polymers) were expanded by doping,27 copolymerization,28–33 and H‐bonded complexation34 with chiral/achiral LC components to induce the particular mesomorphic and electro‐optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Obtained azomethines and poly(azomethines), depending on the chemical structure, emitted mainly blue or green light [1][2][3][4][5][6][7][8][9]. In addition, small compounds and polymers with imine bond are investigated as liquid crystal materials with bent (banana) [10][11][12][13][14] or rod [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] shape. Depending on the chemical structure the investigated compounds exhibited one mesophase or rich polymorphism 34,35].…”
Section: Introductionmentioning
confidence: 99%